Resource Access, Exchange Systems, and Regional Interaction in the Indus Valley: An Investigation of Archaeological Variability at Harappa and Moenjodaro - Fentress, M. A.
Diss.; Cf. Dissertation Abstracts 37 (1976-77) 7182-A.